1991
DOI: 10.1128/jb.173.17.5371-5384.1991
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium lipopolysaccharide modulates infection thread development in white clover root hairs

Abstract: The interaction between Rhizobium lipopolysaccharide (LPS) and white clover roots was examined. The Limulus lysate assay indicated that Rhizobium leguminosarum bv. trifolii (hereafter called R. trifolii) released LPS into the external root environment of slide cultures. Immunofluorescence and immunoelectron microscopy showed that purified LPS from R. tnifolii 0403 bound rapidly to root hair tips and infiltrated across the root hair wall. Infection thread formation in root hairs was promoted by preinoculation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 61 publications
2
56
1
2
Order By: Relevance
“…Another mutant study showed that not only the presence, but also the correct modification, of LPS is needed for optimal nodulation activity (Keating et al, 2002). Furthermore, purified LPS of the microsymbiont has been shown to promote infection in the case of the R. leguminosarum bv trifolii-white clover (Trifolium repens) symbiosis-and to cause the production of novel proteins (Dazzo et al, 1991). The principle of the ability of rhizobial LPS to suppress plant defense responses in the host was achieved by demonstrating the suppression effect on elicitor-induced oxidative burst (Albus et al, 2001).…”
Section: The Lps Of the Microsymbiont S Meliloti Suppresses Elicitormentioning
confidence: 99%
“…Another mutant study showed that not only the presence, but also the correct modification, of LPS is needed for optimal nodulation activity (Keating et al, 2002). Furthermore, purified LPS of the microsymbiont has been shown to promote infection in the case of the R. leguminosarum bv trifolii-white clover (Trifolium repens) symbiosis-and to cause the production of novel proteins (Dazzo et al, 1991). The principle of the ability of rhizobial LPS to suppress plant defense responses in the host was achieved by demonstrating the suppression effect on elicitor-induced oxidative burst (Albus et al, 2001).…”
Section: The Lps Of the Microsymbiont S Meliloti Suppresses Elicitormentioning
confidence: 99%
“…One of the earliest events in the symbiotic dialog involves the secretion of flavonoid compounds by the host plant and the subsequent production of nodulation (Nod) factors by the rhizobia (38). Although the Nod factors are the best-characterized signal molecules of rhizobia, independent evidence supports the view that some of the bacterial surface polysaccharides are also active in signaling the plant (2,16,19,22,39,40,57,60). It has thus been shown that the pretreatment of alfalfa roots with specific fractions of Sinorhizobium meliloti exopolysaccharides (EPS) conferred on symbiosis-deficient EPS mutants the ability to develop nitrogen-fixing nodules at a significant rate (2,22,57,60).…”
mentioning
confidence: 98%
“…Nodulation is still delayed, but the induction of aberrant structures is completely suppressed in the presence of LPS, and, upon release, the nifH-expressing bacteria can divide efficiently, completely fill the infected cells, and provide the plant with nitrogen. Although effects of purified LPSs on root hairs and the efficiency of wild-type nodulation have been reported (32), our data demonstrate a functional extracellular complementation of an LPS mutant. A signaling function in nodule development has been proposed for LPS, mainly as a suppressor of plant defense (6,32).…”
Section: Discussionmentioning
confidence: 79%
“…Although effects of purified LPSs on root hairs and the efficiency of wild-type nodulation have been reported (32), our data demonstrate a functional extracellular complementation of an LPS mutant. A signaling function in nodule development has been proposed for LPS, mainly as a suppressor of plant defense (6,32). Striking similarities exist between the ORS571-oac2 nodules and the indeterminate nodule phenotypes induced by LPS ÏȘ mutants of S. meliloti (33,34) and Rhizobium leguminosarum bv.…”
Section: Discussionmentioning
confidence: 79%